THE ECOLOGICAL IMPERATIVES OF SUSTAINABLE DEVELOPMENT & THE TRANSBORDER REGIONALIZATION PROCESSES (THE POSTSOVIET’ COUNTRIES CASE) - Moreva, Eugenia; Kudina, Marianna; Voronov, Aleksandr; Sergeev, Stepan (Revista Inclusiones, 2019)
The intensification of the negative ecological impacts of a number of economic activities make one to seek for their elimination or nivelation at least treating both as of the primary tasks of the sustainable development provision. With this the necessity to form a public good to manage it efficiently to solve the problem is aggravated in speculative terms because of various of such activities to constitute important economic sectors the environmental impacts of which tend to cover different countries thus to require the transborder regionalization processes to facilitate the innovative actitude of the main stakeholders to overcome efficiently the ecological damages and to provide innovative development. The verification of such deductions is the objective of present paper.